Peaceful Islam Persuasive Dialogue on The Family of Terrorists in the Middle of the Radical Islamic Movement - Abdul Rohman; Abd. Rahman Ambo' Dalle (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2022)
Efforts to deradicalize and counter radicalism based on terrorism have tended only to use an aggressive approach, even though a persuasive dialogical approach is far more significant than using a destructive path. At this point, the study in this article aims to identify in-depth the concepts and techniques offered by NU and Muhammadiyah to families exposed to radicalism. In addition, the analysis in this article also aims to analyze in-depth the strategies carried out by NU and Muhammadiyah based on radicalism in the Lamongan district. The research method used in this article is a descriptive qualitative approach using data collection techniques through in-depth interviews, observation, and documentation. The study results in this article show that, First, NU and Muhammadiyah, in their efforts to prevent radicalism, also apply several approaches, such as persuasive preventive measures mediated by formal educational institutions. Through these institutions, the roles of the two mass organizations intersubjectively convey the impact of the dangers of radicalism in the nation and state. In addition to formal efforts, non-formal and informal approaches are also carried out in preventive actions against the understanding and behavior of radicalism in religion. For example, in the activities of the dhikr assembly, religious lectures, and political activities. Furthermore, in this context, NU and Muhammadiyah, as the largest community organizations in Indonesia, have always been at the forefront of prominent patrons in conveying and warning about the dangers of radicalism, either in the form of brainwashing or in the form of materially beneficial offers. Second, NU and Muhammadiyah, as the largest mass organizations in Indonesia and Lamongan, must be recognized as playing a significant role in deradicalization and counter deradicalism, both of which synergize and join hands in knitting the realization of the theology of rahmatan lil 'alamiin in the terrorism base of Lamongan district. The strategy adopted by NU and Muhammadiyah is a persuasive dialogue with the families of former terrorists who isolate themselves more from the surrounding community. This approach is considered successful in neutralizing the ideologies of radicalism in Lamongan. The Fatayat NU and Nasyiatul Aisyiah institutions are deemed to have played a significant role in realizing this persuasive dialogue with mothers and women from terrorist families.